Flexural response of multi-stiffened aluminium beams in dock platforms. (November 2017) - Chacón, Rolando; Mirambell, Enrique; Arrayago, Itsaso
Abstract: In this paper, the flexural response of extruded wrought aluminium girders is presented. This structural element is intended for usage in marine structures such as light docks, marinas and yacht ports. Ease of use, durability, reduced weight, manoeuvrability and the potential development of bespoke sections are appealing properties in such structures that are fulfilled satisfactorily by this type of aluminium elements. Both experimental and numerical analyses are presented. Experimentally, modules of the girders are tested with loading about both minor and major axes. Numerically, the tests are satisfactorily reproduced for the sake of validation and a subsequent exploitation of the model is addressed for further study of the structural response of the girders. A discussion of the results is presented with some design recommendations of these particular structural elements. Highlights: The flexural response of extruded wrought aluminium girders is presented. Bespoke cross-section according to operational needs are studied. These elements are intended for usage in light marine structures. Both experimental and numerical analyses are presented.